Treatment of Sugar Factory Wastewater with Activated Carbon Produced from Plum Seed Shell - Mon Yi Myo Myint; Zin Marlar Tin San la; Nway Nway Khaing (AI Society & STMIK Indonesia, 2026)
This study demonstrates that activated carbon produced from plum seed shells is an effective adsorbent for treating highly polluted sugar factory wastewater from the Yeni area. The raw effluent was strongly acid (pH 4.5) and contained elevated TSS, TDS, COD (1280 mg/L), and BOD; pH was corrected using sodium hydroxide coagulants 2 ml/ l prior to adsorption. The effluent of pre-treatment is absorbed by plum seed shell activated carbon AC1, AC2, AC3 and AC4 using 10 gm/l. Among them, AC4 is the most effective and the percent removal of sugar factory wastewater parameters are turbidity (80.91%), TDS (42.86%), Colour (50%),COD (75%) and BOD (97.2%) respectively. The treated effluent met Myanmar’s National Environmental Quality Guideline (NEQG) across all measured parameters, supporting the conclusion that plum seed shell activated carbon is both effective and sustainable for sugar factory wastewater remediation. The research may contribute to civil, enviromental engineering and related domains.